PENGARUH METODE READING ALOUD BERBANTUAN BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN KELAS 1 SISWA SEKOLAH DASAR - Ashari, Dinah; Sri Wulan, Neneng; Antik Sari, Nadia Tiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Beginning reading is an important skill that must be mastered by students from an early age, because this is a provision that will be valuable in the learning process. After this initial reading, students will carry out further reading processes, when students experience delays in initial reading, this will affect further reading. The purpose of this study was to determine the effect of the reading aloud method assisted by big book on the ability to read the first grade beginnings of elementary school students, and to find out whether there was an increase in the experimental class better than the control class students. The type used was quasi experiment with nonequivalent control group design. The subjects in the study consisted of 52 grade 1 elementary school students. The instruments used were a beginning reading ability test and an observation sheet. The results of the analysis showed that the effect of reading aloud method assisted by big book on the first grade students' beginning reading ability was 77.4%. The n-gain test results of the experimental class are in the high interpretation and the control class is in the medium interpretation, meaning that students who get the reading aloud method assisted by big books are better than students who get learning with the Alphabet / Spelling method.